Structure of reef fish communities in Gili Noko Island waters, East Java, Indonesia - Ramadhanu, Rizky Akbar; Nugraha, Dimas Rizal Wahyu (Journal of Marine Resources and Coastal Management, 2025)
The coral reef ecosystems around Gili Noko Island, Bawean, Indonesia serve as one of the main sources of livelihood for the local community and provide essential habitat for various marine biota, particularly reef fish. This study aimed to assess the structure of the reef fish community in the area. The research was conducted from April to June 2024 using the Underwater Visual Census (UVC) method. The results recorded the presence of seven reef fish families: Acanthuridae, Apogonidae, Balistidae, Caesionidae, Chaetodontidae, Ephippidae, and Scaridae. The fish abundance index across all station points ranged from 1.50 ind/m² to 1.65 ind/m², indicating a relatively high abundance. The reef fish diversity index (H') at all stations was categorized as high, the evenness index (E) also fell within the high category, while the dominance index (D) was categorized as low. These findings suggest that the reef fish community structure in the waters around Gili Noko Island is both diverse and evenly distributed, with no single species dominating the ecosystem.